Relation of Blood Group, Crowding Index and Family History of Dyspepsia with Helicobacter pylori Infection - Mohammad, Mohammad O.; Ibrahim, Hadeel A.; Karboly, Taha A. Al; Hussein, Hewa A.; Delmany, Abdullah S.; L.Qaradaghi, Aras (Sulaimani Journal for Pure and Applied Sciences, 2016)
Background: Dyspepsia is a common problem that frequently associated with gastritis. The risk of acquiring Helicobacter pylori is related with living conditions and the family's socioeconomic status. Thus, a relation between the H. pylori infection and group O blooded individuals was discovered. Currently, no published data available regarding the association of blood group, crowding index and family history of dyspepsia with H. pylori infection in Kurdistan region. So this study aims to assess the blood group, crowding index and family history of dyspepsia among patients with H. pylori infection. Patients and methodology: Exactly One hundred dyspeptic patients with anti H. pylori Immunoglobulin G (IgG) positive underwent gastroscopy and 75 apparently healthy individuals with no dyspepsia and negative H. pylori IgG antibodies (escorts of patients) using Enzyme-Linked Immuno Sorbent Assay tests (NovaLisa, NovaTec). The samples were collected from Kurdistan Teaching Center for Gastroenterology & Hepatology and Ali Kamal Consultation Clinic in Sulaimani city form December 2012 to March 2014. ABO Blood groups were determined using standardized hemagglutination methods. Results: About 48% of the patients complained of dyspepsia between 1 to 5 years. A significant correlation was found between duration of dyspepsia and the titer of anti H. pylori IgG. The maximum level was found among patients with longer duration (5-15years) of dyspepsia. The most common presentation was epigastric pain (78%) followed by decreasing appetite (39%) and GI bleeding (26%). The most common OGD finding in patients was antral gastritis (59%) followed by duodenal ulcer (21%). Most of the patients had either blood group O (44%) or A (30%) than controls (17.3%, 20%). There was statistically significant (p<0.01), OR = 3.5 (1.3 – 5.2) relation between blood group and H. pylori infection. The majority (70%) of patients had positive family history of dyspepsia than controls (17.3%), with OR=10.5 (2.9 – 37.3). There was significant relation between crowding index and H. pylori infection. The mean crowding index among patients and controls were (4.4 ± 2.3), (2.1 ± 0.9) respectively, with OR= 3.0 (1.9 - 4.9). No significant difference was found between patients and control group regarding age, gender, and marital status. Conclusions: We realized that there was significant association between H. pylori infection and family history of dyspepsia, crowding index and ABO blood group.
Keywords: Dyspepsia; H pylori; blood group; family history; crowding index; KCGH; Sulaimani